The Influence of Transformational Leadership Style and Work Motivation on Employee Performance PT. Sarimelati Kencana - Aurelly, Adelia (Lentera Ilmu Nusantara, 2024)
This study aims to examine the effect of transformational leadership style and work motivation on employee performance at PT. Sarimelati Kencana. Transformational leadership is a leadership style that emphasizes inspiration, motivation, and positive influence on subordinates to achieve organizational goals. This study uses a quantitative approach with data collection techniques in the form of questionnaires, observation and literature study. This research took samples from all employee respondents of PT. Sarimelati Kencana. The analysis methods used are R Square Algorithm analysis and Bootstrapping Path Coefficients analysis on SmartPLS. The partial results of the study show that there is a positive and significanteffect of the Transformational Leadership Style variable on Employee Performance. The partial results of the study show that there is a positive and significant effect of the Work Motivation variable on Employee Performance. The results showed that there was a positive effect simultaneously on the variable Transformational Leadership Style (XI) and Work Motivation (X2) with the Employee Performance variable (Y).